Analog Beamforming and Digital Beamforming on Receive for Range Ambiguity Suppression in Spaceborne SAR - Pingping Huang; Wei Xu (International Journal of Antennas and Propagation)
For future spaceborne synthetic aperture radar (SAR) missions, digital beamforming (DBF) on receive in elevation to form a sharp high receive beam will be adopted to improve the signal to noise ratio (SNR) level and suppress range ambiguities. However, in some special cases, range ambiguities may be received by grating lobes with the high receive beam gain, and range ambiguities would not be well suppressed and even may be increased. In this paper, a new receiving approach based on analog beamforming (ABF) and DBF is proposed. According to the spaceborne SAR imaging geometry and the selected pulse repetition frequency (PRF), the antenna patterns of all subapertures of the whole receive antenna in elevation are adjusted by ABF at first. Afterwards, signals from all subapertures in elevation are combined by a real time DBF processor onboard. Since grating lobes could be suppressed by the antenna pattern of the subapertures via ABF, range ambiguities would be well suppressed even if ambiguities are received by grating lobes. Simulation results validate the proposed approach.